Testis sparing surgery for treatment of small testicular lesions: Is it feasible even in germ cell tumors?. Issue 3 (13th February 2017) - Bojanic, Nebojsa; Bumbasirevic, Uros; Bojanic, Gordana; Vukovic, Ivan; Milojevic, Bogomir; Pekmezovic, Tatjana
Abstract : Background and Objectives: To evaluate the results of testis‐sparing surgery (TSS) in patients, with small testicular lesions and a normal contralateral testicle. Methods: In all, 28 patients were treated with TSS for small testicular lesions and a normal contralateral testicle. TSS was considered in patients with testicular lesions smaller than 2 cm and no evidence of metastatic disease. Results: The mean age of patients was 35.3 ± 7.3 years, while the mean diameter of the testicular lesions was 11.4 ± 3.7 mm. After pathological examination, 18 patients (64.3%) were diagnosed with stromal tumors and miscellaneous lesions, while 10 (35.7%) had a germ cell tumor. The median follow‐up time for the former group was 33 months and no recurrences were observed. In one patient with germ cell tumor, immediate orchiectomy was performed, while the remaining nine were followed‐up (median time, 45 months). One patient developed local recurrence after 39 months. Conclusions: Excellent outcomes for benign lesions could be achieved using TSS. TSS could be offered safely in highly selected patients with germ cell tumors, specifically within a clinical trial but there is more data needed regarding the potential risks and benefits. J. Surg. Oncol. 2017;115:287–290 . © 2016 Wiley Periodicals, Inc.